Wave propagation characteristics in magneto-electro-elastic nanoshells using nonlocal strain gradient theory. (1st September 2018) - Ma, L.H.; Ke, L.L.; Reddy, J.N.; Yang, J.; Kitipornchai, S.; Wang, Y.S.
Abstract: In this paper, the wave propagation in magneto-electro-elastic (MEE) nanoshells is investigated via two nonlocal strain gradient shell theories, namely, the Kirchhoff–Love shell theory and the first-order shear deformation (FSD) shell theory. By using Hamilton's principle, we derive the governing equations, which are then solved analytically to obtain the dispersion relations of MEE nanoshells. Results are presented to highlight the influences of the temperature change, external electric potential, external magnetic potential, external load, nonlocal parameter and length scale parameter on the wave propagation characteristics of MEE nanoshells. It is found that the electro-magneto-mechanical loadings can lead to the cut-off wave number at which the frequency reaches to zero.